Food insecurity situation in Malaysia: findings from Malaysian Adult Nutrition Survey (MANS) 2014 - Ahmad, Muhamad Hasnan; Selamat, Rusidah; Salleh, Ruhaya; Abdul Majid, Nur Liyana; Zainuddin, Ahmad Ali; Mohd Abu Bakar, Wan Azdie; Aris, Tahir (Persatuan Pakar Perubatan Kesihatan Awam, 2020)
Food insecurity affects food intake, and it could prevent an individual from consuming enough nutritious food to support and maintain health. The aim of this paper is to determine the prevalence and factors influencing food insecurity among Malaysian households. In 2014, the Malaysian Adult Nutrition Survey (MANS) was carried out, and one of the components measured was food insecurity. Six out of sixteen questions from the food security core-module questionnaire were adopted and answered by 2962 adults. The results showed that about 25.0% adult experienced food quantity insufficiency, 25.5% had food variety insufficiency, 21.9% practised reduced size of the meal, and 15.2% skipped main meal due to lack of money to spend on. For the parents, 23.7% only rely on cheap food to feed children, and 20.8% could not afford to purchase various foods to feed their children. Location, strata, race, level of education, working status and household income shows significant difference while none of the nutritional status components found to be difference in all six parameters of food insecurity measured. Logistic regression with adjusted odds ratios discovered race, education level and household income were related to risk to all six parameters of food insecurity. In conclusion, food insecurity can be a serious problem in Malaysia. An effective and comprehensive effort by the government in terms of policy solution is required to increase education level and ensure an adequate income for every household. Therefore, future research should focus on some of those promising policy solutions and at the same time, study the other possible underlying factors that may lead to food insecurity.